Water-soluble waterproofing material composition and waterproofing construction method using the same

KR103034840B1Active Publication Date: 2026-10-21GILMAC IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020260094903
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2026-05-26
Publication Date
2026-10-21
Estimated Expiration
2046-05-26

Smart Images

  • Figure 112026063622360-PAT00002_ABST
    Figure 112026063622360-PAT00002_ABST
Patent Text Reader

Abstract

The water-soluble waterproofing material composition according to the present invention relates to a water-soluble waterproofing material composition having an ethylene-vinyl acetate copolymer as the main component and a construction method using the same. By adopting a water-soluble emulsion system, it is environmentally friendly and has the characteristic of exhibiting excellent interfacial adhesion even in environments where some moisture is present on the substrate surface. In addition, it is suitable for construction of parking lots and factory floors where high abrasion resistance and impact resistance are required, and it has the effect of improving the long-term durability of structures by effectively blocking external moisture penetration.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a water-soluble waterproofing material composition used in waterproofing construction in the fields of architecture and civil engineering, and a construction method using the same. More specifically, it relates to a water-soluble waterproofing material composition that is eco-friendly and possesses strong adhesion, excellent durability, and weather resistance. It can be widely applied to waterproofing and repair work on various surfaces such as rooftops, factory floors, parking lots, swimming pools, fish farms, and restrooms, and can be used even in environments where some moisture is present on the substrate, thereby ensuring both construction convenience and reliability of waterproofing quality. Background Technology

[0002] In buildings and civil engineering structures, waterproofing is a critical factor determining the durability and lifespan of the structure. This is because moisture entering from the outside accelerates the corrosion of concrete structures and induces oxidation of internal rebar, ultimately leading to structural defects. Accordingly, various technologies have been developed to form highly reliable waterproofing layers in diverse environments, such as rooftops, exterior walls, underground parking lots, swimming pools, and restrooms.

[0003] One of the most widely used conventional waterproofing technologies is organic film waterproofing agents based on urethane or epoxy. While these materials offer excellent initial waterproofing performance due to their superior elongation and elasticity, they have a fatal drawback: they release large amounts of organic solvents during construction, posing risks to environmental pollution and worker health. Furthermore, organic film waterproofing agents are highly sensitive to moisture; the presence of even minute amounts of water on the substrate can cause a rapid decline in adhesion or peeling, presenting significant limitations in the construction environment.

[0004] To address the limitations of these organic solvent-based technologies, water-soluble or cement-mixed waterproofing materials have been proposed as alternatives. While water-soluble waterproofing materials offer the advantages of being eco-friendly and easy to install, existing products have been criticized for lacking durability for environments subjected to repetitive loads, such as factory floors or parking lots, due to their low abrasion and impact resistance after curing. In particular, industrial sites susceptible to exposure to oil, alkali, and various chemicals, as well as special environments like high-temperature and high-humidity fish farms and swimming pools, require both chemical resistance and long-term thermal stability; however, conventional water-soluble waterproofing materials have struggled to meet these complex requirements.

[0005] Furthermore, in actual construction sites, it is frequently difficult to maintain a perfectly dry substrate. When some moisture remains on the concrete substrate due to weather conditions or site circumstances, most membrane waterproofing technologies fail to form interfacial adhesion with the substrate, often resulting in defects where the waterproofing layer detaches. This applies equally to repair work; removing the existing deteriorated waterproofing layer and applying a new one presents a structural problem in that it requires significant time and cost for substrate preparation and drying.

[0006] Consequently, to extend the lifespan of buildings, a new water-soluble waterproofing technology is required that maintains eco-friendly characteristics by excluding organic solvents, while ensuring strong penetration and adhesion sufficient for application even in harsh environments where moisture is present on the substrate. Furthermore, there is a need to develop a highly durable water-soluble waterproofing composition in which the formed waterproofing film does not merely block water but possesses excellent abrasion resistance, impact resistance, and chemical resistance, thereby maintaining its inherent performance for an extended period even in harsh operating environments such as parking lots and factory floors. Prior art literature

[0007] Korean Registered Patent Publication No. 10-1675862 (2016.11.28) The problem to be solved

[0008] The objective of the present invention is to provide a water-soluble waterproofing material composition that is easy to apply and simultaneously satisfies the oil resistance, water resistance, alkali resistance, and chemical resistance required in various industrial environments.

[0009] Another objective of the present invention is to provide a water-soluble waterproofing composition that ensures long-term durability of a structure by securing high impact resistance and wear resistance capable of withstanding external physical impact or repetitive friction after curing.

[0010] Another objective of the present invention is to provide a water-soluble waterproofing material composition that enables stable application even under harsh field conditions where some moisture remains on the substrate surface to be coated, and can achieve an excellent waterproofing effect through strong interfacial adhesion.

[0011] Another objective of the present invention is to provide an environmentally friendly water-soluble waterproofing material composition that is universally applicable to various environments such as rooftops, factories, parking lots, swimming pools, fish farms, and restrooms. means of solving the problem

[0012] The water-soluble waterproofing material composition according to the present invention comprises an ethylene-vinyl acetic acid copolymer emulsion, cement, sand, and water.

[0013] A water-soluble waterproofing material composition according to one example of the present invention may comprise 10 to 25 weight% of the ethylene-vinyl acetic acid copolymer emulsion, 10 to 30 weight% of the cement, 40 to 65 weight% of the sand, and 5 to 20 weight% of the water.

[0014] A water-soluble waterproofing material composition according to one example of the present invention may have a non-volatile content of 45 to 65 weight%.

[0015] In one example of the present invention, the ethylene-vinyl acetic acid copolymer emulsion is a water dispersion in which ethylene-vinyl acetic acid copolymer particles exist in a colloidal state in water, and the particles may exist at a concentration of 40 to 70 weight%.

[0016] In one example of the present invention, the ethylene-vinyl acetic acid copolymer particles may be copolymerized with 10 to 30 weight% of ethylene and 70 to 90 weight% of vinyl acetic acid, and may have a weight-average molecular weight of 100,000 to 800,000 g / mol.

[0017] In one example of the present invention, the ethylene-vinyl acetate copolymer emulsion may have a glass transition temperature of -15°C to 10°C.

[0018] In one example of the present invention, the sand has an average particle size (D 50 ) can be 0.2 to 1 mm.

[0019] A water-soluble waterproofing material composition according to one example of the present invention may further include core-shell type composite particles, wherein the core-shell type composite particles comprise: a core formed of epoxy resin; an inner shell that seals the core and is polymerized with melamine-formaldehyde; an intermediate layer laminated on the outer surface of the inner shell and formed of a silane-based liquid adhesion promoter; an intermediate shell that seals the intermediate layer and is formed of a methacrylate-methyl methacrylate copolymer; and a porous shell that seals the intermediate shell and is formed of cross-linked sodium polyacrylate.

[0020] In one example of the present invention, in the core-shell type composite particle, the ratio of the diameter of the core, the thickness of the inner shell, the thickness of the intermediate layer, the thickness of the intermediate shell, and the thickness of the porous shell may be 100:1 to 5:5 to 15:5 to 15:10 to 30, and the average particle size of the core-shell type composite particle may be 30 to 150 μm.

[0021] In one example of the present invention, in the core-shell type composite particle, the porous shell reversibly absorbs or releases moisture according to the ambient humidity gradient during the curing of the waterproofing material to suppress rapid drying shrinkage and crack formation inside the waterproofing material; the intermediate shell is selectively dissolved by the increase in pH due to the cement hydration reaction during the curing of the waterproofing material to expose the intermediate layer inside, and the intermediate layer strengthens the interfacial adhesion force to the construction substrate by the liquid adhesion promoter released by the dissolution of the intermediate shell; the inner shell protects the epoxy resin within the core from being released until the waterproofing material cracks; and the core actively seals the cracks by allowing the epoxy resin released upon the inner shell's failure due to cracking of the waterproofing material to flow into and harden within the micro-cracks of the waterproofing material.

[0022] A water-soluble waterproofing material composition according to one example of the present invention may contain 1 to 10 weight percent of the core-shell type composite particles.

[0023] A water-soluble waterproofing material composition according to one example of the present invention may further include additives, and said additives may include one or more selected from dispersants, preservatives, defoaming agents, viscosity modifiers, wetting agents, film-forming agents, pH modifiers, freeze stabilizers, plasticizers, and coupling agents.

[0024] A water-soluble waterproofing material composition according to one example of the present invention may contain the additive in an amount of 0.1 to 5 weight percent.

[0025] A water-soluble waterproofing material composition according to one example of the present invention may have a pH of 4.0 to 6.7.

[0026] A water-soluble waterproofing material composition according to one example of the present invention may have a viscosity of 2,500 to 6,000 mPa·s at 25°C and 1 atm, and a specific gravity of 1.05 to 1.15.

[0027] The present invention provides a waterproof coating formed from the above-mentioned water-soluble waterproofing material composition.

[0028] The waterproof coating according to the present invention may comprise: a base layer, which is a waterproof coating that is adhered to a substrate surface; and a top layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a top layer, which is laminated to the base layer and comprises an ethylene-vinyl acetic acid copolymer emulsion and water.

[0029] The waterproof coating according to the present invention may comprise: a base layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a base layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, which is adhered to a substrate surface; an intermediate layer, which is a waterproof coating laminated on the base layer; and a top layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a top layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, which is laminated on the intermediate layer.

[0030] A waterproof coating according to the present invention may comprise: a base layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a base layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, and a top layer, which is a waterproof coating laminated onto the base layer.

[0031] The present invention provides a method for constructing a waterproofing material using the above-mentioned water-soluble waterproofing material composition.

[0032] A method for constructing a waterproofing material using a water-soluble waterproofing material composition according to any one of paragraphs 1 to 3,

[0033] The waterproofing material application method according to the present invention includes a coating application step of applying the water-soluble waterproofing material composition onto a substrate surface and drying it to form a waterproofing film.

[0034] A waterproofing material construction method according to one example of the present invention may include a primer construction step of forming a primer layer by applying and drying the water-soluble waterproofing material composition on a construction substrate surface, and a topcoat construction step of forming a topcoat layer by applying and drying a water-soluble waterproofing material composition for a topcoat on the primer layer.

[0035] A waterproofing material construction method according to one example of the present invention may include a primer construction step of forming a primer layer by applying a water-soluble waterproofing material composition for a primer layer, comprising an ethylene-vinyl acetic acid copolymer emulsion and water, onto a construction substrate and drying it, and a topcoat construction step of forming a topcoat layer by applying a water-soluble waterproofing material composition for a topcoat layer onto the primer layer and drying it. Here, the water-soluble waterproofing material composition for a topcoat layer refers to the water-soluble waterproofing material composition mentioned earlier.

[0036] A waterproofing material construction method according to one example of the present invention may include a primer construction step of forming a primer layer by applying a water-soluble waterproofing material composition for a primer layer, comprising an ethylene-vinyl acetic acid copolymer emulsion and water, onto a construction substrate and drying it; an intermediate construction step of forming an intermediate layer by applying a water-soluble waterproofing material composition for an intermediate layer onto the primer layer and drying it; and a topcoat construction step of forming a topcoat layer by applying a water-soluble waterproofing material composition for a topcoat layer, comprising an ethylene-vinyl acetic acid copolymer emulsion and water, onto the intermediate layer and drying it. Here, the water-soluble waterproofing material composition for an intermediate layer refers to the water-soluble waterproofing material composition mentioned earlier.

[0037] A waterproofing material application method according to one example of the present invention may further include a surface preparation step for removing and cleaning foreign substances attached to the application surface prior to the primer application step.

[0038] A method for constructing a waterproofing material according to one example of the present invention may further include a preparation step of manufacturing a water-soluble waterproofing material composition prior to the primer construction step. Effects of the invention

[0039] The water-soluble waterproofing composition according to the present invention is very easy to apply and has the effect of simultaneously satisfying mechanical properties (wear resistance, impact resistance, etc.), durability, oil resistance, water resistance, alkali resistance, and chemical resistance required in various industrial environments while maintaining eco-friendly characteristics.

[0040] In addition, the water-soluble waterproofing composition according to the present invention enables stable waterproofing performance without deterioration even in factory floors with a high risk of chemical corrosion or in swimming pools and fish farms where moisture is in constant contact. In particular, it has the effect of maintaining its inherent physical properties for a long period of time even in outdoor exposure environments through excellent weather resistance and stability.

[0041] In addition, the water-soluble waterproofing composition according to the present invention enables application even when some moisture is present on the substrate, thereby minimizing construction delays caused by site conditions, and has the effect of forming an integrated waterproofing layer with the surface to be coated through excellent adhesion performance.

[0042] In addition, the water-soluble waterproofing composition according to the present invention fundamentally blocks moisture penetration and provides the flexibility to omit topcoat or bottomcoat work depending on the process, thereby having the effect of economically reducing construction costs and time.

[0043] In addition, the water-soluble waterproofing material composition according to the present invention has the effect of being universally applicable to various environments such as rooftops, factories, parking lots, swimming pools, fish farms, and restrooms. Brief explanation of the drawing

[0044] Figure 1 is an image showing a top layer and an intermediate layer formed by applying and curing a water-soluble waterproofing material composition according to the present invention onto a standard plate. Figures 2 and 3 are actual images of each step of a waterproofing construction method using a water-soluble waterproofing material composition according to the present invention. Specific details for implementing the invention

[0045] The 'water-soluble waterproofing material composition and waterproofing construction method using the same' according to the present invention will be described in detail below with reference to the attached drawings.

[0046] The drawings described in this specification are provided as examples to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art. Accordingly, the present invention is not limited to the drawings presented and may be embodied in other forms, and the drawings may be exaggerated to clarify the concept of the present invention.

[0047] Unless otherwise defined, technical and scientific terms used in this specification have the meanings commonly understood by those skilled in the art to which this invention pertains, and descriptions of known functions and configurations that could unnecessarily obscure the essence of the invention are omitted in the following description and accompanying drawings.

[0048] The background technology described in this specification is technical information that the inventor possessed or acquired during the process of deriving the present invention, and it cannot be considered as prior art disclosed to the general public prior to the filing of the present invention.

[0049] In some cases in this specification, known structures and devices may be omitted or illustrated in the form of block diagrams focusing on the core functions of each structure and device to avoid obscuring the concept of the invention.

[0050] Expressions such as "comprising," "containing," "having," and "characteristics" mentioned in this specification are open-ended descriptions having equivalent meanings and do not exclude elements, materials, or processes not additionally listed.

[0051] Terms such as 'first', 'second', etc. as used in this specification may be used to describe various components, but the components should not be limited by the terms.

[0052] Unless otherwise specifically indicated, the singular form of a term used in this specification may be interpreted to include the plural form.

[0053] When a component such as a 'membrane', 'film', 'layer', or 'region' mentioned in this specification is described as being on or above another component (e.g., lamination), this includes not only cases where it is directly above in contact with the other component, but also cases where another component is interposed in between.

[0054] The term “layer” as used in this specification means that each material forms a continuum and has a dimension in which the thickness is relatively small compared to the width and length. Accordingly, the term “layer” in this specification should not be interpreted as a two-dimensional flat plane.

[0055] As used in this specification, the term "diameter" refers to the diameter when the shape of the object is circular, and when the shape of the object is non-circular (e.g., polygonal), it is defined as the "equivalent diameter," which is the diameter of a circle having an area equal to the cross-sectional area of ​​the shape. In particular, as the components of the present invention may have a predetermined thickness, the inner diameter based on the inner boundary and the outer diameter based on the outer boundary may differ; therefore, unless otherwise specifically stated in this specification, the "diameter" is interpreted as the "outer surface reference diameter" measured based on the outermost boundary of the object.

[0056] The numerical ranges used in this specification include lower and upper limits and all values ​​within the range, increments logically derived from the form and width of the defined range, all of which are limited values, and all possible combinations of upper and lower limits of numerical ranges defined in different forms. Additionally, unless specifically defined in the specification of this invention, values ​​outside the numerical range that may occur due to experimental error or rounding are also included in the defined numerical ranges.

[0057] Unless otherwise specified, the unit '%' used in this specification means 'weight%'.

[0059] The water-soluble waterproofing composition according to the present invention comprises an ethylene-vinyl acetic acid copolymer emulsion, cement, sand, and water. This water-soluble waterproofing composition forms a waterproofing film through a process of application and curing on a substrate surface. The waterproofing film exhibits excellent physical properties such as waterproofness, durability, and chemical resistance, as well as excellent constructability including convenience, stability, and eco-friendliness during the construction process, and also offers excellent storage stability and economic efficiency before construction. In particular, when the core-shell type composite particles described below are further included, the limitations of a simple passive waterproofing layer are overcome, and durability and chemical resistance are significantly increased by actively responding to external stimuli, with the effect of maximizing long-term maintenance and repair stability.

[0060] The ethylene-vinyl acetate copolymer emulsion (VAE) described above acts as an organic binder in the composition, providing bonding strength between inorganic materials such as cement and sand, and imparting flexibility and adhesion performance to the waterproof coating. Specifically, the ethylene component within the copolymer acts as a permanent plasticizer within the polymer chain; unlike resins with added external plasticizers, there is no phenomenon where the plasticizer leaches out or volatilizes over time, allowing the composition to maintain excellent elongation and low-temperature flexibility over the long term even after curing. This effectively suppresses drying shrinkage of the cement or crack formation caused by external vibrations. Furthermore, the emulsion particles, i.e., the ethylene-vinyl acetate copolymer particles, penetrate into the voids between the hydrate particles generated during the cement hydration process to form a continuous polymer film. These films intertwine with inorganic cement crystals to form an interpenetrating polymer network structure. This simultaneously secures the high compressive strength characteristic of inorganic binders and the elasticity of organic polymers, thereby realizing a waterproof matrix that is resistant to external impacts yet possesses excellent resilience. Furthermore, the vinyl acetic acid functional groups within the copolymer exhibit strong polarity, maximizing hydrogen bonding with the concrete substrate. In particular, by forming a complementary network with the silane adhesion promoter released upon the crushing of the core-shell composite particles described later, it provides stable interfacial adhesion strength that prevents the waterproofing layer from detaching even in wet conditions or harsh external environments. Additionally, as a water-soluble system, the ethylene-vinyl acetic acid copolymer emulsion eliminates the use of volatile organic compounds and hazardous organic solvents. This ensures worker safety and minimizes environmental impact in enclosed underground spaces or construction sites where ventilation is difficult. Moreover, it maintains a chemically stable colloidal state even in the highly alkaline environments of cement, helping to preserve the workability of the paste for extended periods.

[0061] The above ethylene-vinyl acetic acid copolymer emulsion refers to a water dispersion in which ethylene-vinyl acetic acid copolymer particles exist in a colloidal state in water. In this case, it may be preferable for the ethylene-vinyl acetic acid copolymer particles to be present at a concentration of 40 to 70 weight%. If this is satisfied, excellent storage stability can be secured by preventing aggregation or precipitation of polymer particles during the manufacturing and storage of the composition, and work efficiency can be maximized by providing an appropriate level of viscosity and fluidity during construction. Furthermore, as water evaporates during the curing process of the coating film, the polymer particles fuse together to form a dense and uniform continuous polymer film, thereby increasing the bonding strength with cement hydrates and aggregates, which has the effect of simultaneously improving the mechanical strength, elasticity, and moisture barrier performance of the coating film.

[0062] In one example of the present invention, the ethylene-vinyl acetic acid copolymer particles may preferably be copolymerized with 10 to 30 weight% of ethylene and 70 to 90 weight% of vinyl acetic acid. When this is satisfied, the internal plasticizing effect by the ethylene monomer is maximized, thereby providing permanent flexibility to the waterproofing film without the addition of a separate oil-based plasticizer, and in particular, the film does not become embrittled even in low-temperature environments and maintains excellent crack resistance. At the same time, the vinyl acetic acid component with a high specific gravity increases the polarity of the polymer, thereby strengthening interfacial adhesion with concrete and inorganic binders, and has the effect of securing mechanical strength and cohesion of the entire waterproofing layer.

[0063] The above ethylene-vinyl acetate copolymer particles may have a weight-average molecular weight of 100,000 to 800,000 g / mol. If this is satisfied, a tough and resilient waterproof film can be formed through proper entanglement between polymer chains, and the water resistance, heat resistance, and chemical resistance of the coating film can be maintained for a long period.

[0064] The above ethylene-vinyl acetic acid copolymer emulsion has a glass transition temperature (T g It may be preferable for the temperature to be between -15℃ and 10℃. If this is satisfied, the waterproof film does not become embrittled and maintains flexibility not only at room temperature but also in low-temperature winter environments, thereby actively suppressing cracks caused by the behavior of the substrate or thermal shrinkage and expansion. In particular, it prevents phenomena such as the film becoming excessively soft, which lowers mechanical strength, or stickiness occurring at high temperatures, and has the effect of forming a dense continuous film without a separate film-forming agent by securing the lowest film-forming temperature.

[0065] A water-soluble waterproofing material composition according to one example of the present invention may have a non-volatile content of 45 to 65 weight%. When this is satisfied, a sufficient dry film thickness can be secured with only a single application during on-site construction, thereby shortening the construction period and maximizing construction efficiency, and minimizing shrinkage cracks or volume changes caused by excessive moisture evaporation during the curing process.

[0066] A water-soluble waterproofing material composition according to one example of the present invention may have a pH of 4.0 to 6.7. When this is satisfied, the colloidal stability of the ethylene-vinyl acetic acid copolymer emulsion dispersed in the water-soluble matrix can be optimally maintained, and in particular, the intermediate shell of the core-shell type composite particle described below can be prevented from dissolving prematurely during the storage or mixing stage before construction.

[0067] A water-soluble waterproofing material composition according to one example of the present invention may have a viscosity of 2,500 to 6,000 mPa·s at 25°C and 1 atm, and a specific gravity of 1.05 to 1.15. When these conditions are met, excellent workability and smoothness are provided when applied using a roller, brush, or spray, while ensuring an appropriate level of sagging resistance so that the coating does not run down even when applied to vertical walls. In addition, it can help sand and composite particles within the matrix maintain a uniformly suspended state without settling downwards.

[0068] In the water-soluble waterproofing material composition according to the present invention, the content of each component may be at a level capable of achieving the aforementioned effects, and for example, the composition preferably comprises 10 to 25 weight% of the ethylene-vinyl acetic acid copolymer emulsion, 10 to 30 weight% of the cement, 40 to 65 weight% of the sand, and 5 to 20 weight% of the water.

[0069] The sand mentioned above serves as an aggregate and filler in the composition, and plays a pivotal role in forming the volume of the coating film and supporting physical strength after hardening. In particular, by filling the gaps between the inorganic binder, cement, and the emulsion binder, it increases the density of the waterproof coating film and has the effect of preventing cracks by suppressing drying shrinkage that occurs during the curing process.

[0070] At this time, the average particle size (D of the sand) 50 The particle size can be 0.2 to 1 mm. When this is satisfied, an optimal particle size filling effect can be achieved together with the ethylene-vinyl acetic acid copolymer emulsion and cement to form a dense coating structure, and while ensuring work efficiency with a roller during construction, the phenomenon of material separation where the material sinks downward can be effectively prevented.

[0071] A water-soluble waterproofing material composition according to a preferred example may further include core-shell type composite particles. The core-shell type composite particles according to the present invention are dispersed within the composition and serve as intelligent functional additives that actively respond to external stimuli (physical cracking, chemical pH changes, drying shrinkage, etc.).

[0072] The core-shell type composite particle comprises: a core formed of epoxy resin; an inner shell that seals the core and is polymerized with melamine-formaldehyde; an intermediate layer laminated on the outer surface of the inner shell and formed of a silane-based liquid adhesion promoter; an intermediate shell that seals the intermediate layer and is formed of a methacrylate-methyl methacrylate copolymer; and a porous shell that seals the intermediate shell and is formed of cross-linked sodium polyacrylate.

[0073] The inner shell protects the core from releasing epoxy resin until the waterproofing material cracks. When the inner shell is damaged by cracking in the waterproofing material, the released epoxy resin flows into and hardens within the micro-cracks of the waterproofing material, thereby actively sealing the cracks. Specifically, when micro-cracks occur within the waterproofing film due to physical impact or drying shrinkage, the brittle inner shell made of melamine-formaldehyde material is fractured due to stress concentration. At this time, the epoxy resin core is released through the crack gaps and reacts with surrounding unreacted hydrates and binder matrix to harden, thereby physically sealing the cracks and effectively blocking the pathway for moisture penetration.

[0074] The above intermediate shell is selectively dissolved by the increase in pH resulting from the cement hydration reaction during the curing of the waterproofing material, thereby exposing the internal intermediate layer. The liquid adhesion promoter released by the dissolution of the intermediate shell strengthens the interfacial adhesion to the construction substrate. Specifically, when the interior of the matrix is ​​exposed to a strongly alkaline environment (pH 12 or higher) due to the cement hydration reaction, the intermediate shell of the methacrylic acid-methyl methacrylate copolymer containing carboxyl groups reactively dissolves or swells. During this process, the silane-based liquid adhesion promoter of the intermediate layer, which was trapped inside, is released in a timely manner and forms chemical covalent bonds with silica within the construction substrate (concrete), thereby dramatically improving the interfacial adhesion strength. This plays a decisive role in preventing delamination, particularly in wet conditions.

[0075] In addition, the porous shell reversibly absorbs or releases moisture according to the ambient humidity gradient during the curing of the waterproofing material, thereby suppressing rapid drying shrinkage and cracking within the waterproofing material. Specifically, the porous shell formed by the outermost cross-linked sodium polyacrylate absorbs and retains moisture during the mixing and initial stages of construction of the composition. Subsequently, when moisture becomes insufficient during the drying and curing process of the waterproofing film, it gradually releases the retained moisture into the matrix. This internal curing effect minimizes volume changes and drying shrinkage cracks caused by the rapid evaporation of moisture from the cement, and increases the efficiency of the hydration reaction to form a denser waterproofing structure.

[0076] As a result, the core-shell type composite particles according to the present invention have the effect of dramatically improving the durability and reliability of waterproof coatings by establishing an independent yet organic three-stage response system of crack-fracture-healing (inside), alkali-dissolution-adhesion (inside), and drying-release-curing (outside).

[0077] It may be preferable that the average particle size of the core-shell type composite particles be 30 to 150 μm. When this is satisfied, the particles are uniformly dispersed within the composition, thereby providing uniform self-healing and adhesion-enhancing effects throughout the entire waterproof layer. In addition, even within a thin waterproof film of approximately 3 mm, the particles can exist stably within the matrix without protruding.

[0078] At this time, it is preferable that the ratio of the diameter of the core, the thickness of the inner shell, the thickness of the intermediate layer, the thickness of the intermediate shell, and the thickness of the porous shell be 100:1 to 5:5 to 15:5 to 15:10 to 30. When this is satisfied, precise stepwise response to external stimuli is possible without the inherent functions of each layer interfering with one another. Specifically, by controlling the ratio of the inner shell to the core to be thin to 1 to 5, brittleness can be secured to enable immediate fracture upon cracking, and by maintaining the ratio of the intermediate layer to the intermediate shell at 5 to 15, stable preservation of the silane component and dissolution performance within an appropriate time due to alkali can be achieved simultaneously. In particular, the ratio of the outermost porous shell is relatively high at 10 to 30, allowing it to contain sufficient moisture necessary for internal curing.

[0079] The content of the core-shell type composite particles used above may be at a level capable of achieving the aforementioned effect, and for example, it may be preferable for the water-soluble waterproofing material composition to include the core-shell type composite particles in an amount of 1 to 10 weight percent.

[0080] A water-soluble waterproofing material composition according to one example of the present invention may further include additives, and said additives may include one or more selected from dispersants, preservatives, defoaming agents, viscosity modifiers, wetting agents, film-forming agents, pH modifiers, freeze stabilizers, plasticizers, and coupling agents. In this case, the water-soluble waterproofing material composition may include said additives in an amount of 0.1 to 5 weight%. Examples of said dispersants may include one or more selected from polycarboxylates, naphthalenesulfonates, and polyether-modified styrene-maleic anhydride copolymers. Examples of said preservatives may include one or more selected from isothiazolinone derivatives such as benzisothiazolinone (BIT) and methylisothiazolinone (MIT), and sodium benzoate. Examples of the above defoaming agents may include one or more selected from polysiloxane-based, polyether-based, polyglycol-based mixtures, or mineral oil-based compounds. Examples of the above viscosity modifiers may include one or more selected from cellulose derivatives such as hydroxyethylcellulose (HEC) and methylcellulose (MC), and compound-type thickeners such as urethane-modified polyether (HEUR). Examples of the above wetting agents may include one or more selected from polyether-modified silicone-based, sulfosuccinate derivatives, and nonionic surfactants. Examples of the above film-forming agents may include one or more selected from Texanol (2,2,4-trimethyl-1,3-pentanediol monoisobutyrate), butyl carbitol, and glycol ether-based compounds.Examples of the above pH adjusters may include one or more selected from ammonia water, sodium hydroxide (NaOH), and amine-based compounds such as AMP-95 (2-amino-2-methyl-1-propanol). Examples of the above freeze stabilizers may include one or more selected from ethylene glycol, propylene glycol, and glycerin. Examples of the above plasticizers may include one or more selected from phthalate-based compounds such as diisononyl phthalate (DINP) and dibutyl phthalate (DBP), and citrate esters. Examples of the above coupling agents may include one or more selected from organic silane compounds such as 3-glycidoxypropyltrimethoxysilane and vinyltrimethoxysilane, and titanate-based compounds.

[0081] The above method for manufacturing core-shell type composite particles is,

[0082] A first step of manufacturing a microcapsule having an inner shell surrounding a core by introducing a melamine-formaldehyde precursor into an emulsion containing a plurality of droplets formed of liquid epoxy resin and reacting it,

[0083] A second step of spraying a coating solution comprising a methacrylic acid-methyl methacrylate copolymer, a silane-based liquid adhesion promoter, and a solvent onto the outer surface of the microcapsule, and sequentially stacking a liquid silane intermediate layer and a methacrylic acid-methyl methacrylate intermediate shell by inducing phase separation due to a difference in surface energy.

[0084] A third step may be included in which a porous shell is formed on the intermediate shell through powder lamination coating, in which a water-soluble polymer binder solution and cross-linked sodium polyacrylate powder are simultaneously sprayed onto the microcapsule having an intermediate layer and an intermediate shell formed thereon.

[0085] The first step above may include an emulsion forming step of adding a liquid epoxy resin to an aqueous emulsifier solution and emulsifying it to produce an emulsion containing a plurality of droplets, and a shell forming step of introducing a melamine-formaldehyde precursor into the emulsion and reacting it to produce a microcapsule by forming an inner shell that surrounds the epoxy resin as a core and is made of a melamine-formaldehyde material.

[0086] The above emulsion formation step is a step of preparing an emulsion by finely dispersing a liquid epoxy resin in an aqueous solution of an emulsifier using a high-speed stirring device. The aqueous solution of the emulsifier contains an emulsifier and water, and the concentration of the emulsifier may be 0.1 to 5 weight%. Various types of emulsifiers may be used, for example, ethylene-maleic anhydride copolymer may be used.

[0087] The average particle size of the droplets in the emulsion may be 5 to 50 μm. If this is satisfied, the size of the composite particles produced at the end can be precisely controlled within a range suitable for the thickness of the waterproof film, and an optimal balance between the content of the epoxy resin in the core and the thickness of the shell can be secured to ensure reliable self-healing responsiveness in the event of cracking.

[0088] The shell-forming step described above is a step of inducing the introduced melamine-formaldehyde precursor (e.g., methylated melamine resin, etc.) to undergo in-situ polymerization at the epoxy droplet interface. At this time, by adjusting the pH of the reaction system to a range of 3.0 to 5.0 and maintaining the temperature at 50 to 80°C, an inner shell of dense and uniform thickness can be formed.

[0089] The second step described above may be a step of forming a liquid silane intermediate layer and a polymer intermediate shell simultaneously or sequentially on the outer surface of the microcapsules by spraying a specially formulated coating solution while the microcapsules prepared in the first step are suspended in the air using a fluidized bed coater. In particular, in the second step, by inducing phase separation due to the difference in surface energy between components within the coating solution, a double-layered structure can be formed with only a single coating process without the need for separate complex processes.

[0090] As a coating condition for the second stage above, the air supply temperature of the fluid bed coater may be 40 to 60°C. When this is satisfied, the solvent in the sprayed coating liquid volatilizes at an appropriate rate, providing sufficient thermal energy to induce phase separation between the silane and the polymer component, while simultaneously preventing aggregation caused by excessive adhesion to the particle surface. The spraying speed of the coating liquid may be controlled to 5 to 20 g / min, and the spray pressure may be 0.05 to 0.5 MPa. When this is satisfied, the coating liquid is uniformly applied to the surface of the microcapsules in the form of fine droplets to maximize wettability, and each particle can be coated independently to maintain a narrow particle size distribution of the final composite particle.

[0091] As a compositional ratio of the above coating solution, for example, the coating solution may comprise 50 to 100 parts by weight of a silane-based liquid adhesion promoter and 1,000 to 2,000 parts by weight of a solvent per 100 parts by weight of a methacrylic acid-methyl methacrylate copolymer. When this is satisfied, the viscosity of the coating solution can be maintained at a level suitable for fine spraying, and during the process of solvent volatilization, the silane component moves to the inner shell interface of the microcapsule and the methacrylic acid-methyl methacrylate copolymer surrounds the outer surface, causing a phase separation phenomenon to occur most efficiently.

[0092] The above solvent types may include one or more selected from alcohol-based solvents such as ethanol, methanol, and isopropyl alcohol (IPA), and ketone-based solvents such as acetone and methyl ethyl ketone. Preferably, using ethanol allows both the copolymer and the silane component to be uniformly dissolved, while also rapidly volatilizing by the hot air of the fluid bed coater to prevent aggregation between particles.

[0093] The third step above is a step of forming a porous structure by fixing cross-linked sodium polyacrylate powder to the outermost part of the microcapsule in which the intermediate layer and intermediate shell were formed in the second step. Preferably, this is performed by a powder layering coating method in which a liquid water-soluble polymer binder solution is sprayed in a fluid bed coater while fine cross-linked sodium polyacrylate powder is introduced. Through this, the powder particles are physically attached and layered on the surface of the capsule by the binder, thereby forming an outermost shell with a microporous structure capable of absorbing and retaining a large amount of moisture.

[0094] In the third step above, the weight ratio of the water-soluble polymer binder solution and the cross-linked sodium polyacrylate powder may preferably be, for example, 100:50 to 200. When this is satisfied, the powder particles can be laminated on the capsule surface with a sufficient and uniform thickness to form an evenly porous shell, and the powder is firmly fixed without falling off due to the binder.

[0095] The above-mentioned water-soluble polymer binder solution can be prepared by diluting polyvinyl alcohol, hydroxypropylmethylcellulose, or ethylene-vinyl acetic acid emulsion, etc., in water. Preferably, an aqueous polyvinyl alcohol solution with a concentration of 5 to 20 weight% may be used. When this is satisfied, the aqueous solution not only has excellent compatibility with cross-linked sodium polyacrylate powder, but the film formed after drying also has appropriate permeability, thereby providing strong physical support without hindering the absorption and release of moisture into and out of the shell.

[0096] The present invention provides a waterproof coating formed from the above-described water-soluble waterproofing material composition, wherein the waterproof coating may be formed as a single layer, but may be more preferable to have a multilayer structure of two or more layers.

[0097] A waterproof coating with a two-layer structure according to a specific example may include: a base layer, which is a waterproof coating that is adhered to a construction substrate; and a top layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a top layer that is laminated to the base layer and comprises an ethylene-vinyl acetic acid copolymer emulsion and water.

[0098] A three-layer waterproof coating structure according to a specific example may comprise: a base layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a base layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, which is adhered to a substrate surface; an intermediate layer, which is the aforementioned waterproof coating (comprising an ethylene-vinyl acetic acid copolymer emulsion, cement, sand, and water), which is laminated on the base layer; and a top layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a top layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, which is laminated on the intermediate layer.

[0099] A waterproof coating with a two-layer structure according to a specific example may include: a base layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a base layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, and a top layer laminated on the base layer, which is the aforementioned waterproof coating (comprising an ethylene-vinyl acetic acid copolymer emulsion, cement, sand, and water).

[0100] The waterproof coating according to the present invention may have an average thickness of 1 to 8 mm. When this is satisfied, the engineering balance of the entire waterproofing system can be optimized, ranging from securing strong adhesion with the substrate to maintaining durability against the external environment. It may be preferable that the average thickness of the primer layer be 0.05 to 0.5 mm, the average thickness of the intermediate layer be 1 to 5 mm, and the average thickness of the top layer be 0.05 to 0.5 mm. Specifically, when the aforementioned average thickness range of the primer layer is satisfied, the composition can sufficiently penetrate into the micropores of the concrete to exert a physical anchoring effect, thereby preventing detachment at the interface with the substrate. When the aforementioned average thickness range of the intermediate layer is satisfied, a volume is provided in which core-shell type composite particles can be dispersed with sufficient density within the matrix, ensuring substantial self-healing performance in the event of cracking, and the tensile strength and elongation of the waterproofing layer itself can be secured to flexibly respond to the behavior of the structure. When the aforementioned average thickness range of the topcoat layer is satisfied, it performs the role of protecting the lower waterproofing layer from external deterioration factors such as ultraviolet rays and acid rain, and at the same time, during the construction process, the topcoat composition can fill the fine pores on the surface of the intermediate layer to form a dense surface finish.

[0101] The present invention also provides a method for constructing a waterproofing material using the above-mentioned water-soluble waterproofing material composition.

[0102] The waterproofing material application method according to the present invention includes a coating application step of applying the water-soluble waterproofing material composition onto a substrate surface and drying it to form a waterproofing film.

[0103] A waterproofing material construction method according to one example of the present invention may include a primer construction step of forming a primer layer by applying and drying the water-soluble waterproofing material composition on a construction substrate surface, and a topcoat construction step of forming a topcoat layer by applying and drying a water-soluble waterproofing material composition for a topcoat on the primer layer.

[0104] A waterproofing material construction method according to one example of the present invention may include a primer construction step of forming a primer layer by applying a water-soluble waterproofing material composition for a primer layer, comprising an ethylene-vinyl acetic acid copolymer emulsion and water, onto a construction substrate and drying it, and a topcoat construction step of forming a topcoat layer by applying a water-soluble waterproofing material composition for a topcoat layer onto the primer layer and drying it. Here, the water-soluble waterproofing material composition for a topcoat layer refers to the water-soluble waterproofing material composition mentioned earlier (comprising an ethylene-vinyl acetic acid copolymer emulsion, cement, sand, and water).

[0105] A waterproofing material construction method according to one example of the present invention may include a primer construction step of forming a primer layer by applying a water-soluble waterproofing material composition for a primer layer, comprising an ethylene-vinyl acetic acid copolymer emulsion and water, onto a construction substrate and drying it; an intermediate construction step of forming an intermediate layer by applying a water-soluble waterproofing material composition for an intermediate layer onto the primer layer and drying it; and a topcoat construction step of forming a topcoat layer by applying a water-soluble waterproofing material composition for a topcoat layer, comprising an ethylene-vinyl acetic acid copolymer emulsion and water, onto the intermediate layer and drying it. Here, the water-soluble waterproofing material composition for an intermediate layer (comprising an ethylene-vinyl acetic acid copolymer emulsion, cement, sand, and water) refers to the water-soluble waterproofing material composition mentioned earlier.

[0106] The above-mentioned primer application step, the above-mentioned intermediate application step, or the above-mentioned topcoat application step are each steps that form a multi-layered waterproof coating film by being applied independently or organically combined. Each step may adjust the number of applications and drying time according to the moisture condition of the substrate, the ambient temperature, and the required waterproof grade, and may be performed using known application means such as rollers, brushes, or sprays.

[0107] At this time, the water-soluble waterproofing material composition according to the present invention described above may be used in the primer application stage, the intermediate application stage, or the top application stage, and in the stage of applying the remaining layer, a separate water-soluble waterproofing material composition comprising an ethylene-vinyl acetic acid copolymer emulsion and water is used. The separately used water-soluble waterproofing material composition comprises an ethylene-vinyl acetic acid copolymer emulsion and water, and as an example of a composition ratio, it may comprise 30 to 70 weight% of ethylene-vinyl acetic acid copolymer emulsion and 30 to 70 weight% of water. When this is satisfied, it can simultaneously perform the function of a primer that controls the absorbency of the substrate surface and seals pores to maximize adhesion before the application of the main waterproofing layer, and the function of filling fine defects on the surface and providing stain resistance after application.

[0108] A waterproofing material application method according to an example of the present invention may further include a surface preparation step prior to the primer application step, in which foreign substances attached to the surface of the application are removed and cleaned. When this is satisfied, laitance, dust, oil, and various foreign substances that hinder interfacial adhesion between the application surface and the primer layer are blocked in advance, thereby facilitating the smooth penetration of the primer composition into the micropores of the concrete. Consequently, this induces integration with the surface, which determines the durability of the entire waterproofing system, thereby fundamentally preventing the peeling or lifting of the coating film even in harsh environments.

[0109] A waterproofing material application method according to an example of the present invention may further include a preparation step of preparing a water-soluble waterproofing material composition prior to the primer application step. When this is satisfied, by providing an optimal mixing sequence and stirring conditions according to the physical state of each component, material separation can be prevented and a uniform paste-state composition can be secured. As a specific example, by pre-mixing the liquid components and then sequentially adding and stirring the powder components and core-shell type composite particles, etc., premature particle breakage that may occur during the manufacturing process is prevented, and capsules are induced to be uniformly dispersed within the matrix. This enables uniform self-healing performance and physical strength to be exhibited throughout the entire waterproofing film.

[0110] The water-soluble waterproofing composition according to the present invention can be widely applied in various environments where waterproofing is required. In particular, since the water-soluble waterproofing composition according to the present invention is a water-soluble system that does not contain harmful organic solvents and generates almost no volatile organic compounds, it can be installed while ensuring worker safety even in enclosed spaces where ventilation is difficult, such as underground parking lots, utility tunnels, tunnels, water tanks, and indoor restrooms. Furthermore, through the organic combination of a top layer with enhanced weather resistance and an intermediate layer with self-healing performance, it provides long-term waterproofing reliability without deterioration caused by temperature changes or ultraviolet rays, even in externally exposed environments such as rooftops, exterior walls, and bridge decks.

[0111] Examples of construction substrates may include concrete, mortar, PC (Precast Concrete) members, masonry walls (bricks, blocks), stone, ceramic tiles, asphalt, metal plates, and wood. However, to maximize the alkali-responsive adhesion mechanism of the core-shell type composite particles, which are the core components of the present invention, it may be suitable to use a concrete or mortar substrate capable of forming a strongly alkaline environment through a hydration reaction. This is because the intermediate shell of the particles is selectively dissolved to release a silane adhesion promoter, thereby inducing a strong chemical bond with the substrate.

[0113] The present invention will be described in detail through the following examples, but these are intended to explain the invention in more detail and the scope of the present invention is not limited by the following examples.

[0115] <Steps for manufacturing waterproofing material composition>

[0116] A waterproofing material composition was prepared by thoroughly mixing each component according to the mixing ratio in Table 1 below.

[0117] Specifically, the binder, mixing water, and additives of Table 1 below were introduced into a stirrer and mixed at a speed of 500 rpm for 5 minutes to produce a uniform liquid mixture. Subsequently, the inorganic binder of Table 1 below was slowly introduced into the liquid mixture while increasing the stirring speed to 1,000 rpm and stirring sufficiently for 10 minutes to produce a uniform paste-state water-soluble waterproofing material composition.

[0118] Waterproofing film manufacturing steps

[0119] A standard mortar board (150×150 40 mm) according to KS F 2405 was prepared as the construction substrate, and foreign substances such as dust and oil were completely removed from the surface and then dried.

[0120] The above water-soluble waterproofing composition was uniformly applied to the above-mentioned substrate surface using a roller. At this time, the final dry thickness was 3 mm, and to form a uniform film, the composition was applied in layers of 1.5 mm twice. Subsequently, the waterproofing film was formed by curing for 1 to 4 weeks at a temperature of 25°C and a relative humidity of 55%.

[0122] ingredient Content (weight%) bookbinder Ethylene-vinyl acetic acid copolymer emulsion (VINNAPAS) ® 529E, WACKER) 18.0 Inorganic binder Cement (ordinary Portland cement) 18.0 Sand (standard sand, average particle size (D 50 ) 0.6 mm) 54.0 additives Dispersant Aqueous solution of polyether-modified styrene-maleic anhydride copolymer (DISPERBYK-190, BYK) 0.2 Antifoamer Polysiloxane / Polyglycol-based Mixture (BYK-024, BYK) 0.2 Mixing water water 9.6

[0124] A water-soluble waterproofing material composition and a waterproofing film were prepared in the same manner as in Example 1, except that in the step of preparing the waterproofing material composition of Example 1, 4% by weight of core-shell type composite particles prepared in the following step were added to the liquid mixture, and the sand content was changed from 54.0% by weight to 50.0% by weight.

[0126] <Core-Shell Composite Particle Manufacturing Steps>

[0127] 1. Step of manufacturing microcapsules having an inner shell

[0128] In 10 kg of distilled water, the emulsifier ethylene-maleic anhydride copolymer (Zeamac) ® After dissolving 50 g of (60, Vertellus), 2 kg of liquid epoxy resin (YD-128, Kukdo Chemical) was added, and the mixture was emulsified using a homogenizer at 7,000 rpm for 15 minutes to prepare an emulsion containing droplets with an average particle size of 25 μm. To the above emulsion, methylated melamine resin (Cymel ® 350 g of (385, allnex) was added and the pH was adjusted to 3.9 using acetic acid, and then in-situ polymerization was carried out at 65°C for 4 hours while stirring, thereby producing a microcapsule having an inner shell in which the core is made of epoxy resin and the shell surrounding it is made of melamine-formaldehyde.

[0129] 2. Intermediate layer and intermediate shell formation step

[0130] A coating solution was prepared by dissolving 1.5 kg of a methacrylic acid-methyl methacrylate copolymer, in which methacrylic acid and methyl methacrylate are copolymerized in a molar ratio of 1:1.5, and 1 kg of 3-glycidoxypropyltrimethoxysilane, a silane-based liquid adhesion promoter, in 25 kg of ethanol. The coating solution was sprayed while suspending the microcapsules having the inner shells in a fluid bed coater. Here, the weight ratio of the microcapsules to the coating solution was set to 100:15. At this time, through the induction of phase separation due to the difference in surface energy between the silane component and the methacrylic acid-methyl methacrylate copolymer, a liquid silane intermediate layer was formed on the surface of the inner shell of the microcapsules, and an intermediate shell made of methacrylic acid-methyl methacrylate material was laminated on the outer surface, that is, on the surface of the formed intermediate layer.

[0131] 3. Porous shell formation step

[0132] A porous shell was formed on the surface of the microcapsule, which had an intermediate layer and an intermediate shell formed thereon, through powder lamination coating. Specifically, a water-soluble polymer binder solution (an aqueous solution in which polyvinyl alcohol is dissolved at a concentration of 10 wt%) was sprayed onto the surface of the microcapsule, which had an intermediate layer and an intermediate shell formed thereon, while cross-linked sodium polyacrylate powder (AQUAKEEP 10SH-NFC, Sumitomo Seika) with an average particle size of about 10 μm was introduced and adsorbed onto the outermost part of the capsule. Subsequently, the solvent was removed with hot air at 50°C and dried to finally produce a core-shell type composite particle with a multilayer structure having an average particle size of about 80 μm.

[0134] A multilayer waterproof coating was constructed using the waterproofing material composition of Example 1 or Example 2 in the following manner.

[0135] <Background Preparation Step>

[0136] Foreign substances such as dust and oil were completely removed from the surface of the concrete construction base, and then dried.

[0137] Substrate Construction Phase

[0138] The waterproofing composition of Example 1 or Example 2 was uniformly applied to a dried substrate surface using a roller. At this time, the final dry thickness was 3 mm, and to form a uniform film, the coating was applied in two layers of 1.5 mm each. Subsequently, the primer layer was formed by curing for one week at a temperature of 25°C and a relative humidity of 55%.

[0139] <Sangdo Construction Phase>

[0140] A waterproofing composition for a topcoat was uniformly applied over the above-mentioned undercoat using a roller, and then dried for one day at a temperature of 25°C and a relative humidity of 55% to form a topcoat, thereby constructing a waterproofing film with a multilayer structure (2 layers). At this time, the application was performed so that the final dry thickness of the topcoat was 0.1 mm.

[0141] The above-mentioned topcoat waterproofing composition is an ethylene-vinyl acetic acid copolymer emulsion (VINNAPAS ® 10 kg of 529E, WACKER), a wetting agent (BYK-348, BYK), and 10 kg of water were mixed at a speed of 500 rpm for 10 minutes to prepare a homogeneous mixture.

[0143] A multilayer waterproof coating was constructed using the waterproofing material composition of Example 1 or Example 2 in the following manner.

[0144] <Background Preparation Step>

[0145] Foreign substances such as dust and oil were completely removed from the surface of the concrete construction base, and then dried.

[0146] Substrate Construction Phase

[0147] A waterproofing composition for primer was uniformly applied to a dried construction substrate using a roller, and then dried for 3 hours at a temperature of 25°C and a relative humidity of 55% to form a primer layer. At this time, the application was performed so that the final dry thickness of the primer layer was 0.1 mm.

[0148] The above-mentioned waterproofing composition for primer is an ethylene-vinyl acetic acid copolymer emulsion (VINNAPAS ® 10 kg of 529E, WACKER), a wetting agent (BYK-348, BYK), and 10 kg of water were mixed at a speed of 500 rpm for 10 minutes to prepare a homogeneous mixture.

[0149] <Sangdo Construction Phase>

[0150] The waterproofing composition of Example 1 or Example 2 was uniformly applied over the above undercoat using a roller. At this time, the final dry thickness was 3 mm, and to form a uniform coating film, the coating was applied in two layers of 1.5 mm each. Subsequently, a multi-layer (2-layer) waterproofing film was constructed by curing for one week at a temperature of 25°C and a relative humidity of 55% to form a topcoat.

[0152] A multilayer waterproof coating was constructed using the waterproofing material composition of Example 1 or Example 2 in the following manner.

[0153] <Background Preparation Step>

[0154] Foreign substances such as dust and oil were completely removed from the surface of the concrete construction base, and then dried.

[0155] Substrate Construction Phase

[0156] A waterproofing composition for primer was uniformly applied to a dried construction substrate using a roller, and then dried for 3 hours at a temperature of 25°C and a relative humidity of 55% to form a primer layer. At this time, the application was performed so that the final dry thickness of the primer layer was 0.1 mm.

[0157] The above-mentioned waterproofing composition for primer is an ethylene-vinyl acetic acid copolymer emulsion (VINNAPAS ® 10 kg of 529E, WACKER), a wetting agent (BYK-348, BYK), and 10 kg of water were mixed at a speed of 500 rpm for 10 minutes to prepare a homogeneous mixture.

[0158] Intermediate Construction Phase

[0159] The waterproofing composition of Example 1 or Example 2 was uniformly applied over the above primer layer using a roller. At this time, the final dry thickness was 3 mm, and to form a uniform film, the coating was applied in two layers of 1.5 mm each. Subsequently, an intermediate layer was formed by curing for one week at a temperature of 25°C and a relative humidity of 55%.

[0160] <Sangdo Construction Phase>

[0161] A waterproofing material composition for the topcoat was uniformly applied over the intermediate layer using a roller, and then dried for one day at a temperature of 25°C and a relative humidity of 55% to form a topcoat, thereby constructing a waterproofing film with a multilayer structure (3 layers). At this time, the application was performed so that the final dry thickness of the topcoat layer was 0.1 mm. The waterproofing material composition for the topcoat was the same as the waterproofing material for the primer.

[0163] [Experimental Example 1] Evaluation of Self-Healing Performance

[0164] Self-healing performance was evaluated for the water-soluble waterproofing material composition or waterproofing film prepared in Examples 1 and 2.

[0165] Specifically, the above-mentioned waterproof coating was used as a specimen, and an artificial microcrack with a width of 0.3 mm and a length of 50 mm was created in the specimen using a precision cutter. Immediately after the crack was created, a water column 100 mm high was applied to the top of the specimen to measure the initial water permeability. Subsequently, the specimen was left for 7 days in an environment with 60% relative humidity to induce a self-healing reaction, after which a re-permeability test was conducted under the same conditions.

[0167] [Experimental Example 2] Evaluation of Interfacial Adhesion Strength

[0168] The interfacial adhesion strength was evaluated for the water-soluble waterproofing material composition or waterproofing film prepared in Examples 1 and 2.

[0169] Specifically, the above waterproof coating was used as a specimen, and a tensile coupler of 40×40 mm size was attached to the specimen in accordance with the adhesion strength test method of KS F 4934. Then, the adhesion strength was measured after drying and after immersion in water for 24 hours (wet).

[0171] [Experimental Example 3] Evaluation of Drying Shrinkage Reduction and Internal Curing

[0172] The water-soluble waterproofing material composition or waterproofing film prepared in Examples 1 and 2 was evaluated for drying shrinkage reduction and internal curing level.

[0173] Specifically, the above waterproof coating was used as a specimen, and the rate of change in length (drying shrinkage rate) over 28 days was measured in accordance with KS F 2424. In addition, the cross-section of the cured specimen was observed using a scanning electron microscope to analyze the distribution of micropores.

[0175]

Claims

Claim 1 A water-soluble waterproofing material composition comprising an ethylene-vinyl acetic acid copolymer emulsion, core-shell type composite particles, cement, sand, and water, wherein the core-shell type composite particles comprise: a core formed of an epoxy resin; an inner shell that seals the core and is polymerized with melamine-formaldehyde; an intermediate layer laminated on the outer surface of the inner shell and formed of a silane-based liquid adhesion promoter; an intermediate shell that seals the intermediate layer and is formed of a methacrylic acid-methyl methacrylate copolymer; and a porous shell that seals the intermediate shell and is formed of cross-linked sodium polyacrylate. Claim 2 In claim 1, the water-soluble waterproofing material composition comprises 10 to 25 weight% of the ethylene-vinyl acetic acid copolymer emulsion, 1 to 10 weight% of the core-shell type composite particles, 10 to 30 weight% of the cement, 40 to 65 weight% of the sand, and 5 to 20 weight% of the water. Claim 3 delete Claim 4 A water-soluble waterproofing material composition according to claim 1, wherein in the core-shell type composite particles, the ratio of the diameter of the core, the thickness of the inner shell, the thickness of the intermediate layer, the thickness of the intermediate shell, and the thickness of the porous shell is 100:1 to 5:5 to 15:5 to 15:10 to 30, and the average particle size of the core-shell type composite particles is 30 to 150 μm. Claim 5 A water-soluble waterproofing composition according to claim 1, wherein in the core-shell type composite particle, the porous shell reversibly absorbs or releases moisture according to the ambient humidity gradient during the curing of the waterproofing material to suppress rapid drying shrinkage and crack formation inside the waterproofing material, the intermediate shell selectively dissolves due to the increase in pH resulting from the cement hydration reaction during the curing of the waterproofing material to expose the intermediate layer inside, the intermediate layer strengthens interfacial adhesion to the construction substrate by a liquid adhesion promoter released by the dissolution of the intermediate shell, the inner shell protects the epoxy resin inside the core from being released until the waterproofing material cracks, and the core actively seals the cracks by allowing the epoxy resin released when the inner shell is damaged by the cracking of the waterproofing material to flow into and harden inside the micro-cracks of the waterproofing material. Claim 6 A waterproof coating formed from a water-soluble waterproofing material composition according to any one of paragraphs 1 to 2 and 4 to 5. Claim 7 A primer layer, which is a waterproof coating according to claim 6, adhered to a construction substrate; and a top layer, which is a waterproof coating laminated on the primer layer and formed from a water-soluble waterproofing material composition for a top layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water; or a primer layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a primer layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, adhered to a construction substrate; an intermediate layer, which is a waterproof coating according to claim 6, laminated on the primer layer; and a top layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a top layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, laminated on the intermediate layer; or a primer layer, which is a waterproof coating formed from a water-soluble waterproofing material composition for a primer layer comprising an ethylene-vinyl acetic acid copolymer emulsion and water, adhered to a construction substrate. A waterproof coating comprising: a top layer laminated on the above-mentioned underlayer and being a waterproof coating of claim 6. Claim 8 A waterproofing material construction method using a water-soluble waterproofing material composition according to any one of claims 1 to 2 and 4 to 5, comprising a coating construction step of applying the water-soluble waterproofing material composition onto a construction substrate surface and drying it to form a waterproofing film.

Citation Information

Patent Citations

  • Polymer cement composition for waterproofing

    JP2004262748A

  • Waterproofing cement mortar composition

    KR1019980043625A

  • Waterproof of concrete structure and constructingmethod thereof

    KR1020070011853A

  • Light-weight mortar composition for repairing with improved fire proof, durability and workability and construction method of repairing concrete structure using the same

    KR1020210070467A

  • Eco-friendly coating waterproofing composition, coating waterproofing material manufactured therefrom, and construction method thereof

    KR102773164B1